S80 The role of MyD88 in rhinovirus 1B infection. (16th November 2010) - Stokes, C A; Dick, E P; Bennett, J A; Ismail, S; Edwards, M R; Sabroe, I; Parker, LC
Abstract : Introduction: Rhinovirus (RV) are major triggers of acute asthma exacerbations and result in innate immune cell infiltration into the airways. Viral recognition by TLRs results in activation of pathways mediated by the adaptors MyD88 and TRIF, which predominantly control the production of proinflammatory cytokines and interferons respectively. We have previously shown that addition of the cytokine IL-1 (which also signals via MyD88) potentiates responses to the viral mimic Poly (I:C), 1 which acts in a MyD88-independent manner. This demonstrates the potential for IL-1signaling to impact on viral infection. In this study, we explored the ability of MyD88 to regulate responses to the natural viral pathogen, RV serotype 1B (RV-1B). Methods: MyD88 was stably knocked down in the immortalised bronchial epithelial cell line, BEAS-2B, using a lentiviral transduction system containing shRNA targeted to MyD88. Wildtype or MyD88 KD cells were stimulated, in the presence or absence of human monocytes, with TNFα and IL-1β, poly(I:C), LPS and gardiquimod (TLR3, TLR4 and TLR7/8 agonists, respectively), or infected with RV-1B. Selected experiments were carried out in the presence of IL-1ra. Changes in cytokine release were measured by ELISA. Rates of viral replication were measured using quantitative PCR. Results: Costimulation of BEAS-2B cells with IL-1 and RV-1B caused a dramatic increase in proinflammatory (CXCL8), but not CCL5 production. MyD88 KD cells with ∼70% reduction in MyD88 mRNA levels showed no impairment to TNFα or poly(I:C) stimulation, but significantly reduced responses to IL-1β. MyD88 KD cells also had significantly impaired responses to RV-1B as assessed by production of CXCL8 and CCL5. Inhibition of RV-induced CXCL8 production could also be achieved by pre-treatment with the IL-1 antagonist, IL-1ra. IL-1β was not produced from RV-infected cells, implicating other members of the IL-1 family in the response of epithelial cells to viral infection. Viral replication was more marked in MyD88 KD cells. Conclusion: A reduction in MyD88 signalling modulates specific epithelial cell responses to rhinovirus, and thus may be an important target to control acute inflammation induced by human viral pathogens.